Use of biochar-based column filtration systems for greywater treatment: A systematic literature review. (August 2022) - Quispe, J.I. Bautista; Campos, L.C.; Mašek, O.; Bogush, A.
Abstract: Biochar-based column filtration systems (BCFS) for greywater treatment have gained attention in the last decade. However, a review of the state-of-the-art on this subject has not been conducted, leaving the analysis and limitations of the available research still unexplored. This paper reviews the current literature to give insights into the technology and identify new areas of investigation. This study used a systematic review approach to evaluate the documentation relating to the technology's worldwide status, configuration, removal mechanisms, removal efficiency, and water reuse applications. In total, 28 studies were reported in 16 countries including India and Sweden as leading ones. Three filter column configurations were identified: single biochar filter, multilayer filter, and polishing step in the treatment chain. The pollutant removal efficiency of BCFS ranged between 50 and 99%. Treated greywater is reused mainly for non-potable purposes such as toilet flushing, cloth washing, and crop irrigation. Overall, this technology can be a feasible and sustainable alternative for greywater treatment and application in water-scarce regions. However, further research is needed on social perception toward potable water reuse, new feedstocks for biochar production, the scaling-up and long-term assessment, evaluation of additional water microbial indicators, and the modification of biochar to target specific water reuse purposes. Graphical abstract: Unlabelled Image Highlights: The systematic review identified 28 studies on BCFS conducted during 2010–2021. BCFS remove greywater pollutants in the range of 50–99% and allow water recycling. Use of treated greywater for non-potable purposes is the main water reuse strategy. BCFS can provide access to clean water and good health to water-scarce regions. New research areas were identified to expand the treated water reuse applications.